2018
DOI: 10.1136/bmjopen-2017-019502
|View full text |Cite
|
Sign up to set email alerts
|

Single-arm, open-label, dose-escalation phase I study to evaluate the safety of a herbal medicine SH003 in patients with solid cancer: a study protocol

Abstract: IntroductionCancer is a major health problem worldwide and the leading cause of death in many countries. The number of patients with cancer and socioeconomic costs of cancer continues to increase. SH003 is a novel herbal medicine consisting of Astragalus membranaceus, Angelica gigas and Trichosanthes Kirilowii Maximowicz. Preclinical studies have shown that SH003 has therapeutic anticancer effects. The aim of this study is to determine the maximum tolerated dose of SH003 in patients with solid cancers.Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…SH003 is a herbal formula comprising three medicinal herbs, Astragalus membranaceus (Am), Angelica gigas (Ag), and Tk. Accumulating evidence has demonstrated that SH003 has anti-cancer efficacy against various types of cancer [35,36,45], and clinical trials have been conducted to analyze the efficacy and safety of SH003 in patients with solid cancers [32,53]. The effect of SH003 in chemotherapy-induced neuropathic pain has been demonstrated in docetaxel-induced mechanical allodynia [54]; however, its effect on paclitaxel has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SH003 is a herbal formula comprising three medicinal herbs, Astragalus membranaceus (Am), Angelica gigas (Ag), and Tk. Accumulating evidence has demonstrated that SH003 has anti-cancer efficacy against various types of cancer [35,36,45], and clinical trials have been conducted to analyze the efficacy and safety of SH003 in patients with solid cancers [32,53]. The effect of SH003 in chemotherapy-induced neuropathic pain has been demonstrated in docetaxel-induced mechanical allodynia [54]; however, its effect on paclitaxel has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…SH003 is a complex formula composed of an ethanol extract of three medicinal herbs, namely Astragalus membranaceus, Angelica gigas, and Trichosanthes kirilowii Maximowicz [32]. Previous studies have reported its anti-cancer effects on various types of cancer cells, such as breast, lung, and prostate cancer [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The study protocol was previously published before study completion. We followed the methods described by Cheon et al 17…”
Section: Study Design and Ethical Approvalmentioning
confidence: 99%
“…e anticancer effect of SH003 against breast, lung, and prostate cancer has been demonstrated through several in vitro and in vivo studies [30][31][32][33][34][35][36][37][38]. e safety of SH003 was proved by phase I clinical study for solid tumors, and phase II clinical study for wildtype EGFR lung cancer patients is in progress [39][40][41]. Meanwhile, phase I/II clinical study of SH003 combined with docetaxel for breast and lung cancer patients is also in progress (NCT01755923, https://clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%